2005
DOI: 10.1111/j.1600-0463.2005.apm_01.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis Transmission, role in genital tract infection and pregnancy outcome: an enigma

Abstract: Whether bacterial vaginosis (BV) is acquired from an endogenous or an exogenous source is subject to controversy. Despite findings of an association between sexual behaviour and BV, some data indicate that BV is not a sexually transmitted infection in the traditional sense, while other data indicate that BV is an exogenous infection. A third aspect of BV is its tendency to go unnoticed by affected women. All of this will have a strong impact on how physicians view the risks of asymptomatic BV. This review focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 80 publications
(67 reference statements)
0
65
0
3
Order By: Relevance
“…Symptoms of BV can include a thin greyish-white vaginal discharge with a foul odour, and mild irritation. Of more concern is that BV is associated with serious disorders, such as pelvic inflammatory disease (Sobel, 2000;Larsson et al, 2005) and adverse pregnancy outcomes, such as preterm delivery, low birth weight and post-partum endometritis. BV also increases the risk of male-to-female, and female-to-male, HIV transmission (Schmid et al, 2000).…”
mentioning
confidence: 99%
“…Symptoms of BV can include a thin greyish-white vaginal discharge with a foul odour, and mild irritation. Of more concern is that BV is associated with serious disorders, such as pelvic inflammatory disease (Sobel, 2000;Larsson et al, 2005) and adverse pregnancy outcomes, such as preterm delivery, low birth weight and post-partum endometritis. BV also increases the risk of male-to-female, and female-to-male, HIV transmission (Schmid et al, 2000).…”
mentioning
confidence: 99%
“…It may also be attributed to the difference in socio-economic and hygienic level of people. Some studies have found a relationship between BV and high-risk behaviours associated with sexually transmitted infections (STIs) such as early sexual debut and multiple sex partners (Larsson, et al, 2005). According to Olartan (2006), asymptomatic BV occurred relatively more frequently in females as compared with males and it is a major criterion of urinary tract infection (UTI).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the presence of BV increases the risk for human immunodeficiency virus infection [12]. It is noteworthy that many women with BV do not show any symptoms [13], pelvic inflammatory disease [14], infections following gynecological surgery [15] and pre-term birth. BV is not transmitted through toilet seats, bedding, swimming pools, or touching of objects.…”
Section: Introductionmentioning
confidence: 99%
“…The second systemic treatment for BV is oral clindamycin. The one known clinical trial conducted describing the efficacy of oral clindamycin reported that a 300-mg, twice-daily course of clindamycin for 7 days resulted in a 94 percent cure rate [15]. The two topical treatments for BV include metronidazole 0.75 percent vaginal gel and clindamycin 2 percent vaginal cream [5].…”
Section: Introductionmentioning
confidence: 99%